New SIRT1 activator from alkaline hydrolysate of total saponins in the stems-leaves of Panax ginseng. Issue 22 (15th November 2015) - Ma, Li-Yuan; Zhou, Qi-Le; Yang, Xiu-Wei
Graphical abstract: Abstract: Two new dammarane-type triterpenes, namely ginsenoslaloside-I [3β, 12β, 24 S -trihydroxy-dammara-20(22) E, 25-diene-3- O -β-d -glucopyranoside, 1 ] and 20( S )-ginsenoside-Rh1 -6′-acetate (2 ), together with twelve known compounds (3 –14 ) were isolated from the alkaline hydrolysate of total saponins of the stems-leaves of Panax ginseng C.A. Meyer. Their chemical structures were elucidated by extensive spectroscopic analyses and comparison with the reported data. All 14 compounds were evaluated for their anti-proliferative activities against two human cancer cell lines (HL-60 and Hep-G2) and promotion activities of SIRT1. Compound6 exhibited significant inhibitory activity in a concentration-dependent manner against HL-60 and Hep-G2 with the IC50 values of 10.32 and 24.33 μM, respectively, and had comparable IC50 values with those of vinorelbine, a positive control agent. Meanwhile, compounds1 and6 were found to be a potential activator of SIRT1. The preliminary structure–activity relationship was also discussed based on the experimental data obtained.